Development and In-vitro evaluation of poly (lactic acid) films for controlled release studies of Lapatinib: an anticancer drug - Chandra Babu Allu, Sudhakar Poluru, Siraj Shaik, Subha MCS, Chowdoji Rao Kashayi (Journal of Applied Pharmaceutical Science, 2014)
Biodegradable poly (lactic acid) films containing Lapatinib were prepared by spreading polymer / Lapatinib solution on the non-solvent surface. Different drug loading polymer films can be obtained by controlling the weight ratios of drug and polymer. The synthesized Lapatinib loaded PLA films were evaluated by different parameters such as drug loading, encapsulation efficiency, surface morphology, differential scanning calorimetry, powder X-ray diffractometry and In vitro drug release kinetics. Various combinations of the polymer-drug weight ratios were used to achieve In vitro release of drug over a period of 30-35 days, with initial burst release
Keywords: poly (lactic acid),Lapatinib,films,biodegradable,controlled release.